Improved Ferroelectric Performance of Mg-Doped LiNbO3 Films by an Ideal Atomic Layer Deposited Al2O3 Tunnel Switch Layer - Zhang, Yan; Ren, Qing Hua; Chai, Xiao Jie; Jiang, Jun; Yang, Jian Guo; Jiang, An Quan (Nanoscale research letters, 2019)
Bilayer structures composed of 5% Mg-doped LiNbO 3 single-crystal films and ultrathin Al 2 O 3 layers with thickness ranging from 2 to 6 nm have been fabricated by using ion slicing technique combined with atomic layer deposition method. The transient domain switching current measurement results reveal that the P-V hysteresis loops are symmetry in type II mode with single voltage pulse per cycle, which may be attributed to the built-in electric field formed by asymmetric electrodes and compensation of an internal imprint field. Besides, the inlaid Al 2 O 3 , as an ideal tunnel switch layer, turns on during ferroelectric switching, but closes during the post-switching or non-switching under the applied pulse voltage. The Al 2 O 3 layer blocks the adverse effects such as by-electrode charge injection and improves the fatigue endurance properties of Mg-doped LiNbO 3 ferroelectric capacitors. This study provides a possible way to improve the reliability properties of ferroelectric devices in the non-volatile memory application.